2,2′-Bipyridin-1′-ium 1-oxide bromide monohydrate - Heintz, Katharina (Acta Crystallogr E Crystallogr Commun, 2018)
The title compound 2,2′-bipyridin-1′-ium 1-oxide bromide crystallizes as a monohydrate, C(10)H(9)N(2) (+)·Br(−)·H(2)O. Structural disorder is observed due to the fact that protonation, as well as oxidation, of the N atoms of 2,2′-bipyridine occurs at either of the N atoms. The disorder extends to the remainder of the cation, with a refined occupancy rate of 0.717 (4) for the major moiety. An intramolecular N—H⋯O hydrogen bond forces the bipyridine unit into an s-cis conformation. Each pair of neighbouring 2,2′-bipyridin-1′-ium ions forms a dimeric aggregate by hydrogen bonds between their respective N—O and the N—H functions. These dimers and hydrogen-bonding interactions with bromide ions and the water molecule give rise to a complex supramolecular arrangement.